Pelatihan Pemahaman Literasi Keuangan, Penyusunan Laporan Keuangan Sederhana dan Pemasaran Online pada UMKM di SMK Negeri 2 Denpasar - mandala, i gusti ngurah agung kepakisan (Journal of Social Service and Empowerment, 2025)
ABSTRACT Community Service Program titled “GENBIZ TOUR: Generation Business Tour” was held at SMK Negeri 2 Denpasar with the aim of providing training for students as prospective Micro, Small, and Medium Enterprise (MSME) entrepreneurs. The training focused on three main aspects: improving financial literacy, preparing simple manual financial statements, and developing product marketing strategies through digital platforms. This activity involved students from the Accounting Department as a form of experiential learning. Based on observations, many MSMEs in the creative industry sector still focus on short-term decision-making, which hinders sustainable business development. The lack of structured access to information on financial record-keeping and digital marketing strategies remains a major challenge for MSME owners.The training materials were prepared using secondary data from both established MSMEs and those in the start-up phase. The content covered the importance of financial literacy, manual transaction recording techniques, data entry, and the preparation of basic financial statements such as income statements, balance sheets, and cash flow statements. In addition, participants were trained to utilize digital media to market their products and expand their market reach. The results of the training produced several recommendations: the need to instill financial literacy from an early age through regular and systematic bookkeeping habits, the importance of implementing proper financial records as the basis for accurate report preparation, and the necessity of follow-up training on digital marketing strategies so that MSMEs can adapt and compete in the digital transformation era. Keywords: community service, MSMEs, financial literacy, simple financial statements, digital marketing   ABSTRACT   Program pengabdian kepada masyarakat bertajuk GENBIZ TOUR: Generation Business Tour diselenggarakan di SMK Negeri 2 Denpasar dengan tujuan memberikan pelatihan kepada siswa-siswi sebagai calon pelaku Usaha Mikro, Kecil, dan Menengah (UMKM). Pelatihan ini difokuskan pada tiga aspek utama, yakni peningkatan literasi keuangan, penyusunan laporan keuangan sederhana secara manual, serta strategi pemasaran produk secara digital. Kegiatan ini melibatkan siswa jurusan Akuntansi sebagai bentuk pembelajaran berbasis praktik (experiential learning). Berdasarkan hasil observasi, banyak UMKM di sektor industri kreatif masih berorientasi pada keputusan jangka pendek, sehingga menghambat pengembangan usaha secara berkelanjutan. Minimnya akses terhadap informasi yang terstruktur mengenai pencatatan keuangan dan strategi pemasaran digital menjadi tantangan utama yang dihadapi oleh pelaku UMKM. Materi pelatihan disusun berdasarkan data sekunder dari UMKM yang telah berjalan maupun yang sedang dalam tahap perintisan. Materi mencakup pentingnya literasi keuangan, teknik pencatatan transaksi manual, penginputan data, hingga penyusunan laporan keuangan dasar seperti laporan laba rugi, neraca, dan arus kas. Selain itu, peserta juga dilatih untuk memanfaatkan media digital dalam memasarkan produk guna memperluas jangkauan pasar. Hasil pelatihan ini menghasilkan beberapa rekomendasi, yaitu perlunya menanamkan literasi keuangan sejak dini melalui kebiasaan pencatatan keuangan yang teratur dan sistematis, pentingnya penerapan pencatatan keuangan sebagai dasar penyusunan laporan yang akurat serta, dibutuhkannya pelatihan lanjutan mengenai strategi pemasaran digital agar UMKM mampu beradaptasi dan bersaing di era transformasi digital. Kata kunci: pengabdian kepada masyarakat, UMKM, literasi keuangan, laporan keuangan sederhana, pemasaran digital